Safety of Aspirin Use in Patients With Stroke and Small Unruptured Aneurysms. (5th January 2021) - Weng, Jian-Cong; Wang, Jie; Du, Xin; Li, Hao; Jiao, Yu-Ming; Fu, Wei-Lun; Huo, Ran; Yan, Zi-Han; Xu, Hong-Yuan; Wang, Shuo; Cao, Yong; Zhao, Ji-Zong
Abstract : Objective: We initiated a multicenter, prospective cohort study to test the hypothesis that aspirin is safe for patients with ischemic cerebrovascular disease (ICVD) harboring unruptured intracranial aneurysms (UIAs) <7 mm. Methods: This prospective, multicenter cohort study consecutively enrolled 1, 866 eligible patients with ICVD harboring UIAs <7 mm in diameter from 4 hospitals between January 2016 and August 2019. Baseline and follow-up patient information, including the use of aspirin, was recorded. The primary endpoint was aneurysm rupture. Results: After a total of 4, 411.4 person-years, 643 (37.2%) patients continuously received aspirin treatment. Of all included patients, rupture occurred in 12 (0.7%). The incidence rate for rupture (IRR) was 0.27 (95% confidence interval [CI] 0.15–0.48) per 100 person-years. The IRRs were 0.39 (95% CI 0.21–0.72) and 0.06 (95% CI 0.010–0.45) per 100 person-years for the nonaspirin and aspirin groups, respectively. In the multivariate analysis, uncontrolled hypertension and UIAs 5 to <7 mm were associated with a high rate of aneurysm rupture, whereas aspirin use was associated with a low rate of aneurysm rupture. Compared with other groups, the high-risk group (UIAs 5 to <7 mm with concurrent uncontrolled hypertension) without aspirin had higher IRRs. Conclusion: Aspirin is a safe treatment for patients with concurrent small UIAs and ICVD. Patients who are not taking aspirin in the high-risk group warrant intensive surveillance. ClinicalTrials.gov Identifier: NCT02846259. Classification of Evidence: This study provides Class III evidence that for patients harboring UIAs <7 mm with ICVD, aspirin does not increase the risk of aneurysm rupture.